Thermodynamics analysis of an absorption refrigeration system utilizing LiBr - H2O mixture for a grain silo - Silveira, José Luz; Júnior, Luiz Carlos Martinelli (Revista Ciências Exatas, 2008)
The main difficulty in grain conservation is in the preservation of theirs nutritional proprieties and keep them free of insects, fungus and consequences. The insects control have had realize by insecticide in spite of toxics residuals, but the other losses, how the fungus and metabolic activity are controlled by aeration. In bad conditions, the soybean grain consume yourself and further heating in the mass. The ideal conditioning occur in low temperatures, where the metabolic activity is reduced and the fungus and insects don’t appear. How the grain storage systems have dryers burning firewood and the ARS works using as main source the residual heat of processes or of the combustion of several fuels, in this paper is applied the First and Second Law of Thermodynamics to study an Absorption Refrigeration System (ARS) operating with LiBr-H2O mixture to a soybean grain silo.